Systems biomedicine : concepts and perspectives - Liu, Edison T.; Lauffenburger, Douglas A.; ScienceDirect eBooks (London : Academic, 2009)
Systems biology is a critical emerging field that seeks to define the interactions of all biological components by examining underlying biochemical and genetic processes. It is a discipline that quantifies and annotates the complexity of biological systems in order to construct algorithmic models to predict outcomes from component input. Applications in medicine are revolutionizing our understanding of biological processes and systems. Systems Biomedicine is organized around foundations, computational modelling, network biology, and integrative biology, with the extension of examples from human biology and pharmacology, to focus on the applications of systems approaches to medical problems. An integrative approach to the underlying genomic, proteomic, and computational biology principles provides researchers with guidance in the use of qualitative systems and hypothesis generators. To reflect the highly interdisciplinary nature of the field, careful detail has been extended to ensure explanations of complex mathematical and biological principles are clear with minimum technical jargon.
I. Foundations of Systems Biology -- Genomic Technologies for Systems Biology -- Proteomic Technologies -- II. Computational Modeling of Biological Systems -- Dynamic Systems Analysis -- Spatio-temoral Modeling of Cellular Systems -- High-level modeling of biological networks -- High-Performance Computing -- Modeling Software -- III. Network Biology -- Protein Interaction Networks -- Signaling Networks with Modeling Strategies -- Protein networks in integrin-mediated adhesions -- Network Imaging -- RNAi networks -- IV. Integrative Biology of Higher Biosystems -- Signal Processing and Integration During Development -- Systems Biology and Stem Cell Biology -- Application of immunologic modeling in drug discovery and development -- V. Systems Medicine Applications -- Systems Pharmacology.
Print version record.
Elsevier
Keywords: Systems biology; Medical sciences -- Computer simulation; Medical sciences -- Computer simulation; Systems biology; Systems Biology; Computer Simulation; Biomathematik; Medizin; Systembiologie; Electronic books